Lilium martagon L. in former manor parks and Protestant cemeteries in the central part of Polish Pomerania - Sobisz , Zbigniew; Truchan, Mariola (Biodiversity: Research and Conservation, 2006)
The occurrence of Lilium martagon in former manor parks and Protestant cemeteries was studied. The species was found in 7 former manor parks i.e. Borkowo, Ciemino, Dąbrówka Bytowska, Duninowo, Mołtowo, Zaleskie, Zdrzewno, and in 7 Protestant cemeteries situated in villages Budowo, Bukowo Morskie, Chotkowo, Kluki, Kopaniewo, Roszczyce, Smołdzino. The size of its populations varied from a few to around 1000 individuals.